Romanian Medical Informatics and Professor Jan H. van Bemmel’s Support - Mihalas, G. I. (Methods of Information in Medicine, 2006)
Objective: The development of medical informatics education in Romania, starting from Timisoara, was strongly influenced by the support offered generously by Professor Jan H. van Bemmel, in a period when the imposed political conditions limited contacts between Western and Eastern countries. We tried to present here some of the most significant actions and events related to this long lasting collaboration.Methods: The evolution of the relations between the Departments of Medical Informatics from Medical University in Timisoara and Erasmus University in Rotterdam is described in chronological order.Results: Professor van Bemmel found appropriate ways to offer his support, adapted to each historical period. He started by sending books, journals and software, continued with support for attending conferences and then extended to more active collaborations.Conclusion: In 2006 professor van Bemmel was the keynote speaker of the EFMI Special Topic Conference held in Timisoara and was awarded the title of “Doctor Honoris Causa” of the Victor Babes University of Medicine and Pharmacy.
Keywords: Medical informatics education; EFMI; IMIA